Pengembangan Multimedia Interaktif Berbasis Midnjet Mindmanager pada Materi Plantae untuk Siswa Kelas X SMA - Arifuddin, Nur Ummu Pratiwi; Karim, Hilda; Adnan, Adnan (Biology Teaching and Learning, 2019)
Abstract. This study aims to develop learning media products in the form of interactive multimedia based on Mindjet MindManager which combines several media (text, images, animated videos and interactive quizzes) for biology of plantae material or plant world. This study uses the Research and Development (R & D) method using the ADDIE development model, namely analysis (analyze), design (design), development (implementation), implementation (implementation), and evaluation (evaluation). Mind manager-based Mindjet-based interactive multimedia products are focused on the varied learning process and the activity of students in learning. This development aims to produce interactive multimedia products that are valid and practical. The data collection tool used is in the form of validity assessment and practicality instruments. The assessment results from expert validators show that the products developed are feasible to use and obtain a validity value of 4.3 with a percentage value of 85% that meets the validity standard and can be used as a learning medium. Teachers and students also show a positive response to interactive multimedia. The practicality of the media obtained teacher responses with a value of 94.2% and responses of students with a value of 87.9% (very practical). Based on the results of the study it can be concluded that the interactive multimedia learning media developed are valid and practical, and feasible to be applied in the learning system.Keywords: interactive multimedia, mindjet mindmanager, ADDIE, valid, practical